Transcriptomic analysis of seed development in Paysonia auriculata (Brassicaceae) identifies genes involved in hydroxy fatty acid biosynthesis - Hu, Hao; Swift, Armond; Mauro-Herrera, Margarita; Borrone, James; Borja, Guadalupe; Doust, Andrew N. (Frontiers in Plant Science, 2023)
Paysonia auriculata (Brassicaceae) produces multiple hydroxy fatty acids as major components of the seed oil. We tracked the changes in seed oil composition and gene expression during development, starting 14 days after flowers had been pollinated. Seed oil changes showed initially higher levels of saturated and unsaturated fatty acids (FAs) but little accumulation of hydroxy fatty acids (HFAs). Starting 21 days after pollination (DAP) HFA content sharply increased, and reached almost 30% at 28 DAP. Total seed oil also increased from a low of approximately 2% at 14 DAP to a high of approximately 20% by 42 DAP. We identified almost all of the fatty acid synthesis and modification genes that are known from Arabidopsis, and, in addition, a strong candidate for the hydroxylase gene that mediates the hydroxylation of fatty acids to produce valuable hydroxy fatty acids (HFAs) in this species. The gene expression network revealed is very similar to that of the emerging oil crop, Physaria fendleri, in the sister genus to Paysonia. Phylogenetic analyses indicate the hydroxylase enzyme, FAH12, evolved only once in Paysonia and Physaria, and that the enzyme is closely related to FAD2 enzymes. Phylogenetic analyses of FAD2 and FAH12 in the Brassicaceae and outgroup genera suggest that the branch leading to the hydroxylase clade of Paysonia and Physaria is under relaxed selection, compared with the strong purifying selection found across the FAD2 lineages.